1997
DOI: 10.1292/jvms.59.1075
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of LPS-Induced Tumor Necrosis Factor in Calves Treated with Chlorpromazine or Pentoxifylline.

Abstract: ABSTRACT. The inhibitory effect of chlorpromazine (CPZ), pentoxifylline (PTX) and dexamethasone (DEX) was investigated in a model of endotoxin shock in Holstein calves following an intravenous administration of Esherichia coli endotoxin (LPS). Initial correlations with its effects on the levels of tumor necrosis factor (TNF), a pivotal mediator of endotoxin shock, and clinical signs were obtained. The pretreatment of CPZ or DEX significantly decreased the serum levels of TNF, and reduced endotoxic shock. But t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…PTX inhibited the mRNA expression of inflammatory cytokines in humans and mice [5,13], suggesting that PTX might have different pharmacologic effects in cattle. Previous studies reported that PTX did not inhibit the production of cytokines in cattle [8].…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…PTX inhibited the mRNA expression of inflammatory cytokines in humans and mice [5,13], suggesting that PTX might have different pharmacologic effects in cattle. Previous studies reported that PTX did not inhibit the production of cytokines in cattle [8].…”
mentioning
confidence: 78%
“…Inhibition of cytokine-gene expression was useful in the therapy of various gram-negative bacterial infections such as pneumonia and enteritis [9,14]. We have previously demonstrated that chlorpromazine (CPZ) and dexamethasone (DEX) reduced the increased TNF levels following Escherichia coli endotoxin challenge in calves, and pentoxifylline (PTX) did not reduce the increased TNF levels [8]. The purpose of the present study was to investigate the effects of CPZ, DEX, and PTX on the expression of proinflammatory cytokines in bovine peripheral blood mononuclear cells (PBMCs).…”
mentioning
confidence: 99%
“…Thus, the development of a sepsis model with welldefined respiratory dysfunction is important both as a tool to understand the pathogenesis of the disorder and as a model to test potential interventions. Different experimental approaches have been used to study pulmonary dysfunction in sepsis, among them CLP (17) and injection of LPS (18). The CLP model has been used very often because it mimics human peritoneal sepsis (17).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of IL-1 was confirmed according to the inhibition or reduction of its activity by goat anti-human IL-1 antibody. For the IL-6 assay, serum samples were treated at 56°C for 30 min and then assayed for proliferative activity on IL-6-dependent MH60/BSF2 cells using rhIL-6 as a standard [17].…”
Section: Methodsmentioning
confidence: 99%
“…TNF-α, in particular, plays a critical role in the pathogenesis of septic shock syndrome induced by endotoxemia [2,18]. During the course of septicemia and experimental endotoxemia, initiation of the cytokine network by TNF-α is followed by activation of other mediator systems, which is thought to be a major mediator to the development of septic shock syndromes, i.e., systemic inflammatory response syndromes (SIRS) [2,[16][17][18]25]. The undetectable TNF-α in the affected cattle in the present study might be attributed to low concentration of serum endotoxin or tolerance condition against endotoxin [2,19,25].…”
Section: Facs Analysis Of Pbmcsmentioning
confidence: 99%